Patterns of healthcare utilisation for respiratory complications of adults with neuromuscular disease: a population study. Issue 3 (18th September 2018) - Rose, Louise; McKim, Douglas; Leasa, David; Nonoyama, Mika; Tandon, Anu; Bai, Yu Qing; Amin, Reshma; Katz, Sherri; Goldstein, Roger; Gershon, Andrea
Our objective was to quantify health service utilisation including monitoring and treatment of respiratory complications for adults with neuromuscular disease (NMD), identifying practice variation and adherence to guideline recommendations at a population level. We conducted a population-based longitudinal cohort study (2003–2015) of adults with NMD using hospital diagnostic and health insurance billing codes within administrative health databases. We identified 185 586 adults with NMD. Mean age 52 years, 59% female. 41 173 (22%) went to an emergency department for respiratory complications on average 1.6 times every 3 years; 14 947 (8%) individuals were admitted to hospital 1.4 times every 3 years. Outpatient respiratory specialist visits occurred for 64 084 (35%) with four visits every 3 years, although substantial variation in visit frequency was found. 157 285 (85%) went to the emergency department (all-cause) almost 4 times every 3 years, 100 052 (54%) were admitted to hospital. Individuals with amyotrophic lateral sclerosis/motor neurone disease (ALS/MND) had more emergency department visits compared with other types of NMD (p<0.0001). One-third of adults with NMD received respiratory specialist care at a frequency recommended by professional guidelines, although substantial variation exists. Emergent healthcare utilisation was substantial, emphasising the burden of NMD on the healthcare system and urgent need to improve community and social supports, particularly for ALS/MND patients. One-third of adults with neuromuscular disease received specialist respiratory care. Emergent healthcare use was substantial, emphasising an urgent need to improve community and social supports. http://ow.ly/FluZ30leuLk